Deconstruction of Gendered Dialogues in English Language Students Textbook for Grade 12 Senior High School - Putu Yasamahadewi; Ni Komang Arie Suwastini; Putu Suarcaya (UNIB Press, 2023)
Education plays a significant role in maintaining or deconstructing patriarchal gender constructions in society. Within this ambivalent arena, this study aimed to analyze the representation of gender constructions in a textbook for grade 12 Indonesian EFL students published by the Ministry of Education of the Republic of Indonesia in 2018. The textual analysis proposed by McKee is used to analyze the data. Language functions attributed to the two genders are used as the parameters to find their feminine or masculine depiction based on Lakoff (1973) and Coates (2013) combined with Millet’s Sexual Politics. The study revealed that the textbook shows gender deconstructions towards language functions used in female-only, male-only and mixed sex dialogues. The deconstruction of the stereotypes can be seen from the presence of feminine traits in male characters, such as asking for information and producing more phatic and expressive utterances than females. In contrast, female characters are depicted to be dominantly produced masculine traits, such as being knowledgeable by giving more information than men and dominating in conversations. Although, at some points, the characters are still associated with stereotyped gender traits, the efforts to deconstruct traditional images of both genders need to be appreciated even though they still seem ambivalent.